SUBVERTING STEREOTYPES: A CRITICAL STUDY OF P. PADMARAJAN’S UDAKAPPOLA (1978) - MENON, APARNA S; B, MEENU (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this paper is to critically analyse the 1978 Malayalam novel Udakappola, written by P Padmarajan. The novel follows the life and actions of people who belong to the underbelly of society. From a self-loathing pimp to a retired government officer, Padmarajan weaves a story that chronicles the everyday life of a group of people who do not conform to the stereotypes and prejudices set by society. The characters and their actions are not easily accepted by the moral sense of the general public. Through the unnamed narrator, Padmarajan unfolds the lives of these people who live on the ‘other side’ of the society.The paper is an attempt to study the various themes discussed by Padmarajan in the novel, and how Padmarajan successfully manages to paint an honest picture of a maligned class of society.